Disorder and spectral line shapes in two-level systems - Shi, Wu-Jun (2014)
Using a stochastic model, we examine disorder-induced changes in the absorption line shape of a chromophore embedded in a matrix of noninteracting two-level systems (TLSs) with randomly oriented dipole moments. By systematically controlling the degree of TLS positional disorder, a perfectly crystalline, glassy or a combination of the two environments is obtained. The chromophore is assumed to interact with TLSs via long-range dipole–dipole coupling. At long times and in the absence of disorder, Gaussian line shapes are found, which morph into Lorentzian for a completely disordered environment owing to strong coupling between the chromophore and a TLS in close vicinity.